2016
DOI: 10.13045/acupunct.2016051
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Assessment Tools in Clinical Trials for Patients Injured in Traffic Accidents in South Korea

Abstract: Objectives : Theaimofthisstudyistoreviewtheinstrumentsusedtoassesspatientcondition andtheeffectsofKoreanmedicaltreatmentforpatientsinjuredintrafficaccidentsinclinical studiesintheKoreanmedicalfieldpublishedinSouthKorea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…; and mental symptoms such as unclean spirit, palpitations, anxiety and irritability, insomnia, fear, and etc. KM treatment can be expected to be effective for patients with traffic accidents by eliminating static blood at the injured site and regulating the worsening blood circulation [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; and mental symptoms such as unclean spirit, palpitations, anxiety and irritability, insomnia, fear, and etc. KM treatment can be expected to be effective for patients with traffic accidents by eliminating static blood at the injured site and regulating the worsening blood circulation [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many reports of KM treatment for musculoskeletal diseases caused by traffic accidents [1][2][3][4] , there have been few cases reported in relation to the degree of obesity or systemic symptoms such as edema, heavy body feeling, and abdominal fullness. In this study, we observed the synergistic effect of wild ginseng complex (WGC) pharmacopuncture combined with KM automobile insurance treatment on two obese female patients with an occurring heavy body feeling, edema, digestive discomfort, dizziness and abdominal fullness during hospitalization after traffic accident.…”
Section: Introductionmentioning
confidence: 99%